The confessions of Saint Augustine - Saint, Bishop of Hippo; Defilippis, Leonardo (Beaverton, OR : Saint Luke Productions, 1983)
Leonardo Defilippis recounts the story of the conversion of the brilliant Augustine of Hippo (354-430 AD). Confused by his mother's devotion to Christianity and his father's paganism, Augustine is caught for many years in a depraved and immoral existence. Intellectual pride, indecision, and lack of trust prevent him from changing his ways, until he is finally persuaded to read a passage from the Scripture, whereupon he is irresistibly drawn to Christ.
Keywords: Augustine, -- Saint, Bishop of Hippo; Catholic Church -- Algeria -- Hippo (Extinct city) -- Bishops -- Drama; Christian saints -- Algeria -- Hippo (Extinct city) -- Drama